2018
DOI: 10.3390/inorganics6040124
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Study of AlF3 and ACF Surfaces

Abstract: By applying first principles density functional theory (DFT) methods, different metal fluorides and their surfaces have been characterized. One of the most investigated metal fluorides is AlF3 in different polymorphs. Its chloride-doped analogon AlClxF3−x (ACF) has recently attracted much attention due to its application in catalysis. After presenting a summary of different first-principle studies on the bulk and surface properties of different main group fluorides, we will revisit the problem of the stability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 84 publications
(94 reference statements)
2
13
1
Order By: Relevance
“…Locally, the structural motifs found by Bailey [20] and ours agree well, as proven by similar frequency shift obtained for CO. Contrary to the model of Bailey et al, the (0001) surface model used in this work shows threefold coordinated aluminium centers due to the usage of a different theoretical set-up and no additional fluorides [21].…”
Section: Introductioncontrasting
confidence: 67%
See 4 more Smart Citations
“…Locally, the structural motifs found by Bailey [20] and ours agree well, as proven by similar frequency shift obtained for CO. Contrary to the model of Bailey et al, the (0001) surface model used in this work shows threefold coordinated aluminium centers due to the usage of a different theoretical set-up and no additional fluorides [21].…”
Section: Introductioncontrasting
confidence: 67%
“…For both surface models, the theoretical results are in the range of the experimental data [20]. Our previous investigations [21] have shown that the (01 12) surface is quite high in energy and only another layer of fluorides and surface reconstruction stabilizes the α-AlF 3 -(01 12) surface. Locally, the structural motifs found by Bailey [20] and ours agree well, as proven by similar frequency shift obtained for CO.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations